Effects of 1 versus 2 games a week on physical and subjective scores of Subelite Soccer Players - Rollo, I.; Impellizzeri, F. M.; Zago, M.; Iaia, F. M. (International Journal of Sports Physiology and Performance, 2014)
The physical-performance profiles of subelite male footballers were monitored during 6 wk of a competitive season. The same squad of players played either 1 (1G, n = 15) or 2 (2G, n = 15) competitive matches per week. On weeks 0, 3, and 6, 48 h postmatch, players completed countermovement jump (CMJ), 10- and 20-m sprints, the Yo-Yo Intermittent Recovery Test (YYIRT), and the Recovery-Stress Questionnaire. Both groups undertook 2 weekly training sessions. The 2G showed after 6 wk lower YYIRT (-11% to 3%, 90% CI -15.8% to -6.8%; P < .001) and CMJ performances (-18.7%, -21.6 to -15.9%; P = .007) and higher 10-m (4.4%, 1.8-6.9%; P = .007) and 20-m sprints values (4.7%, 2.9% to 6.4%; P < .001). No differences were found at 3 wk (.06 < P < .99). No changes over time (.169 < P < .611) and no differences time × group interactions (.370 < P < .550) were found for stress, recovery, and the Stress Recovery Index. In conclusion players` ability to sprint, jump, and perform repeated intense exercise was impaired when playing 2 competitive matches a week over 6 wk.